Impacts on freshwater macrophytes produced by small invertebrate herbivores: Afrotropical and Neotropical wetlands compared - Franceschini, M. Celeste (2020)
We compare invertebrate herbivory upon 13 macrophyte species in freshwater wetland systems located in two global ecozones, the Afrotropics and Neotropics, in the context of biotic and environmental factors influencing these wetlands. The two ecozones are climatically similar regions, with similar water chemistry, but experience contrasting grazing and disturbance pressures from large mammalian herbivores. Our results for macrophytes show that small invertebrates removed significantly more lamina biomass per leaf in Neotropical macrophytes (6.55%) than Afrotropical ones (4.99%). Overall, the results indicate that underestimation of up to 15.6% of leaf biomass may occur if plant tissue removal by invertebrate herbivores is not included in estimates of plant biomass. Regarding the contrasting grazing and disturbance pressures from large herbivores influencing these wetlands, seven mammal species (especially the Black Lechwe antelope, Kobus leche) were observed impacting macrophytes in the Afrotropical wetlands, while in the Neotropics, only much smaller rodents, capybara, (Hydrochoerus hydrochaeris) were sporadically observed. We discuss the relevance of results for invertebrate herbivory in the context of both the methodological approach and the importance of large mammalian herbivores as biotic factors additionally impacting macrophyte populations in these subtropical to tropical wetlands.